Comparative Study on Teacher Training Education Policy and Practices in Qurâanic Schools: Case of Semi-Urban Rural and Remote Rural Settings in Banjarnegara Regency - Astuti, Wiji; Kusakabe, Tatsuya (Sebelas Maret University, 2016)
This paper aims at describing the recent status of teacher training education policy and practices in 12 purposely selected Qurâanic Schools in 4 villages, which belong to Banjarnegara Regency in Central Java Province in Indonesia. The data was obtained through a field survey by using questionnaire instrument and open-ended interview to 12 school principals and 20 teachers of the Qurâanic schools. Teachersâ status degree at semi-urban rural area is more educated while the teachers at remote rural area are graduates from Qurâanic school who have no teacherâs certificate. In both areas, teachers mainly develop their professional teaching skills by self-learning due to very few in-service teacher trainings. Unlike teachers at formal schools, who are often offered teaching training by educational bureau in regency or province level, teachers at Qurâanic schools almost never receive teaching training. This findings suggest the local government to conduct intensive teacher training program for Quranic schools teachers in order to achieve better Islamic educational services.